L’accord de proximité du déterminant en français - Anne Abeillé; Aixiu An; Aoi Shiraïshi (Discours)
Contemporary French is often considered to have lost closest conjunct agreement, contrary to other Romance languages (Corbett, 1991), hence recent debates about French feminine visibility (Michel, 2016; Viennot, 2017). We consider the coordination of determiners and nouns in the Noun Phrase with different number or gender in large written corpora (Frantext, FrWaC). We show that closest conjunct agreement is alive and even favoured in some cases. We conclude by some remarks on gender agreement and word order.